PROW jako źródło środków finansowych umożliwiających rozwój obszarów wiejskich - Bórawski, Piotr (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The objective of the paper was to recognize the structure of PROW in the years 2004–2006 and 2007–2013. Moreover the allocation of PROW in particular provinces was presented. The analysis of collected material proves that the most financial measures was directed for the support of agricultural activity on areas about adverse conditions of the management, fulfillment of direct payments and farms adjustment to European Union standards. But, in the 2007–2013 the most financial measures was directed for the improvement of competitiveness of agricultural and forest sector and the improvement of natural environment and rural areas. The descriptive methods were used in the paper